Financial Frictions, Foreign Direct Investment, and Growth - Luis San Vicente Portes (FIW - Research Centre International Economics, 2010)
This paper assesses the role of financial frictions and Foreign Direct Investment (FDI) on an economys growth rate, business cycle volatility, and firms capital structure. We gauge these effects within the Financial Accelerator framework, where entrepreneurs can establish affiliates of local firms abroad through Foreign Direct Investment. Model simulations suggest that in the presence of credit market imperfections FDI is associated with faster growth, less leverage, and lower aggregate volatility. These features are consistent with the macroeconomic dynamics of the more globally integrated economies over the last three decades.
Keywords: F43; E32; G32; 330; Output volatility; Foreign Direct Investment; International Diversification; Capital Structure